PENGEMBANGAN MODUL MATEMATIKA BERBASIS GAMIFIKASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA MATERI OPERASI HITUNG DASAR DAN PECAHAN - Setiawan, Rudy; Wijaya, Elita Mega Selvia (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
Mathematics is an important subject in elementary school (SD) because it trains logical thinking and problem-solving skills for students. However, many students find math difficult and boring so their motivation to learn is low. This research aims to develop gamification-based mathematics modules on basic and fractional calculation operation materials to improve the understanding of elementary school students' concepts. The method used is Research and Development (R&D) with the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The analysis was carried out through observation and interviews with teachers at SDN Dinoyo 1 Malang. Design includes designing modules with gamification elements such as points, badges, challenges, and leaderboards. Development was carried out using Articulate Storyline and Canva Education, then validated by material and media experts with results suitable for use with minor revisions. The implementation will be carried out in June 2025 involving 30 students in grades IV-V. Evaluation shows pretest-posttest results with an average increase student score of 18.5 points (p<0.05). The student response was very positive, 92% stated that learning was fun and helped with concept understanding. Teachers also assessed that the modules facilitate the delivery of material and improve student learning activities. The conclusion of this study is that gamification-based mathematics modules are effectively used to improve the understanding of the concept of basic and fractional calculation operations in elementary school students.